Juridical Analysis of Police Authority for Community Protection of Robberies that Occurred in Batam City (Research Study in the Barelang Police Legal Area) - Simanjuntak, Victor Daniel; Fadlan, Fadlan; Prasetyasari, Christiani; Fadjriani, Lia (CV. Rayyan Dwi Bharata, 2023)
In writing this thesis entitled Juridical Analysis of police authority to protect the public from robbery that occurred in Batam City. One form of crime that often occurs in society is the crime of motor vehicle theft. Motor vehicle theft is a crime against property that is not uncommon in developing countries. The phenomenon of violent theft of two-wheeled motorized vehicles or what is better known as